2005
DOI: 10.1080/10611860500230294
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface protein docked vesicular carrier for site specific delivery to liver

Abstract: The intrinsic liver tropism of liposomes can be augmented by the addition of targeting features such as the incorporation of hepatotropic elements of the hepatitis viruses. Hepatitis B virus is known to infect hepatocytes after viremia by asialoglycoprotein receptor mediated uptake. However, the specificity of hepatitis B virus surface protein (HBsAg) towards hepatocytes has confronting reports. In the present study, we evaluated the functional ability of HBsAg to be employed as a ligand for targeting hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A significantly higher β-galactosidase activity was found in liver relative to other organs, including lung, kidney, skin and heart 24 and 48 h after administration. Hepatitis B virus surface protein (HBsAg) has been used to develop liposomes with strict hepatotropism [58]. The covalently linked to the surface of nanoparticles for active targeting [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher β-galactosidase activity was found in liver relative to other organs, including lung, kidney, skin and heart 24 and 48 h after administration. Hepatitis B virus surface protein (HBsAg) has been used to develop liposomes with strict hepatotropism [58]. The covalently linked to the surface of nanoparticles for active targeting [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…In the infectious condition, HBV particles bind with the plasma membranes of hepatocytes, which is a crucial step of viral entry [18]. The viral envelope is composed of three polypeptides, classified as small, middle and large surface proteins, which play important roles in reorganization of receptors on hepatocytes followed by internalization [20]. Study of the HBV genome demonstrated that basically four genes are encoded by this genome, that is C, X, P and the hepatitis B surface antigen gene.…”
Section: Hepatitis B: Chronic Liver Diseasementioning
confidence: 99%
“…Extensive studies have been conducted using HBV as a carrier system [18][19][20] and its surface envelope proteins as delivery systems 17,21,22 or targeting moieties. 23,24 However, their application is severely constrained by the safety of viral carriers 25 and the strong immunogenicity of extrinsic proteins. 26,27 The envelope protein of HBV consists of large (L), middle (M), and small (S) proteins.…”
Section: Introductionmentioning
confidence: 99%